2004
DOI: 10.1353/csd.2004.0003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Campus Climate for Gay, Lesbian, Bisexual, and Transgender (GLBT) Students Using a Multiple Perspectives Approach

Abstract: In this study we compared perceptions of the campus climate for GLBT students from surveys returned by 80 GLBT students, 253 general students, 126 faculty members, 41 student affairs staff members, and 105 residence hall assistants. A snowball sampling strategy was used to collect GLBT student responses, all residence hall assistants were surveyed, and a stratified random sampling process was used for faculty, student affairs staff, and general students. Some survey scales were common across all groups and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 24 publications
3
109
1
3
Order By: Relevance
“…Eliason 1996;Malaney, et al 1997;Brown et al 2004). In addition to the published work, several US institutions (Indiana University; Kansas State University; University of Arizona) have undertaken assessments of campus climate with reports of their findings widely available (e.g.…”
Section: Homophobia On Campusmentioning
confidence: 99%
“…Eliason 1996;Malaney, et al 1997;Brown et al 2004). In addition to the published work, several US institutions (Indiana University; Kansas State University; University of Arizona) have undertaken assessments of campus climate with reports of their findings widely available (e.g.…”
Section: Homophobia On Campusmentioning
confidence: 99%
“…While it varied depending on academic program, previous research found that student affairs staff members were more aware of issues than were faculty members, with findings indicating a greater knowledge of sexual minority topics and events amongst the student affairs staff when compared to the faculty (R. D. Brown et al, 2004). Clear policies that faculty and staff are aware of can assist them in recognizing and addressing these issues whenever observed, as well as being receptive to students who bring up such issues with them.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are echoed repeatedly throughout the literature, with studies telling the same story of LGBT students facing higher levels of harassment, fear for personal safety, and reporting the concealment of their sexual and gender identities to avoid intimidation (Brown et al, 2004;Ellis, 2009;Gortmaker & Brown, 2006;McKinney, 2005;Rankin, 2005;Waldo, 1998). While all of these studies share the limitations of small sample sizes, and some do not cover transgender students, the students' experiences reported by all of them are remarkably similar.…”
Section: Harassment and Safety On Campusmentioning
confidence: 89%
“…This is echoed by the findings Ellis (2009), andBrown et al (2004), who also found that perceptions of campus climate varied between faculty, staff, graduates and undergraduates, and also that lesbians found the campus climate more hostile than gay men. Gortmaker & Brown (2006) found significant differences in lesbian and gay students' perception of campus climate based on how "out" the individuals were, with out students reporting a more negative campus climate than those who were closeted.…”
Section: General Campus Climatementioning
confidence: 96%